Decision support system for determining the best tofu industry location using a simple multi-attribute rating technique - Julianto Lemantara (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The tofu industry has significant potential in Indonesia, particularly as a staple food rich in protein. However, many entrepreneurs face challenges in determining the optimal location to build a tofu industry. Suboptimal locations often cause various problems, including high operational costs, difficult access to raw materials, and negative environmental impacts due to production waste. Factors such as raw material availability, waste management, distance to residential area, land cost, and accessibility are the main challenges that must be considered in determining the optimal location of the tofu industry. This study used the Simple Multi-Attribute Rating Technique (SMART) method to support objective decision-making in determining the best location for the tofu industry. Using this method, the determination of the best alternative location for the tofu industry is evaluated based on the weight of the specified criteria. The research results indicated that the Decision Support System (DSS) application that implemented the SMART method could provide the best location recommendations. The accuracy of the SMART method calculation on the DSS application is 100% correct and can be trusted. In addition, the DSS application was also able to accommodate criteria modeling with dynamic assessment scales according to user needs.